Measuring Training Contribution: Organization Design on a Training Evaluation System based on Return of Training Investment - Nafia Kusuma Indrayati; Fendy Suhariadi (Psikostudia : Jurnal Psikologi, 2023)
Competition that occurs in the port service industry makes companies strive to create superior and professional quality human resources. To increase the capacity and capability of employees, PT. X was quite determined during the HR development process with the aim that employees have the potential to become a talent company, through work program plans, one of which is education and training. However, these human resource development efforts were not followed up with training evaluations resulting in the uncertainty of the effectiveness and contribution of the program to individual and company performance. This study aims to develop an evaluation process to determine the effectiveness and contribution of education and training programs. This study refers to the Phillips Return of Investment Model to develop a training evaluation design. The results of the study show that the Training Return-of-Investment (ROTI) intervention in the form of a standard operating procedure (SOP) is accepted by users and can be used as a reference for implementing HR development through training evaluations for companies. Meanwhile, the evaluators can provide evaluation guidelines and assignments during the training evaluation session. The results of training programs cannot always be measured in monetary terms, so this training evaluation activity can also measure intangible benefits.Persaingan yang terjadi pada industri pelayanan kepelabuhan membuat perusahaan berupaya menciptakan kualitas SDM yang unggul dan professional. Dalam rangka meningkatkan kapasitas dan kapabilitas karyawan, PT. X cukup bertekad selama proses pengembangan SDM dengan tujuan karyawan berpotensi tersebut menjadi talent perusahaan, melalui rencana program kerja salah satunya pendidikan dan pelatihan. Namun upaya pengembangan SDM tersebut tidak diikuti dengan evaluasi pelatihan mengakibatkan tidak diketahui secara pasti efektivitas dan kontribusi program tersebut terhadap kinerja individu hingga perusahaan. Penelitian ini bertujuan untuk menyusun proses pelaksanaan evaluasi untuk mengetahui efektivitas dan kontribusi program pendidikan dan pelatihan. Penelitian ini mengacu pada Phillips Return Of Investment Model untuk menyusun rancangan evaluasi pelatihan. Hasil penelitian menunjukkan bahwa intervensi Training Return-of-Investment (ROTI) dalam bentuk standard Operating Procedure (SOP) diterima oleh user dan dapat menjadi referensi acuan pelaksanaan pengembangan SDM melalui evaluasi pelatihan ke perusahaan. Sedangkan kepada para evaluator dapat memberikan panduan dan penugasan evaluasi selama sesi evaluasi pelatihan berlangsung. Hasil program pelatihan tidak selalu dapat diukur ke nilai uang/moneter sehingga kegiatan evaluasi pelatihan ini juga dapat mengukur manfaat yang bersifat intangible (tidak terlihat).